Mundkur Memorial Award Lecture - Integrated management of potato Sclerotium wilt caused by Sclerotium rolfsii - ANAHOSUR, K.H. (Indian Phytopathology, 2002)
At the outset I offer my gratitude to the Indian Phytopathological Society for having given me this opportunity to deliver the Mundkur Memorial Lecture. I consider it both a privilege and honour. My teachers during my graduating programme in early sixties in Plant Pathology courses narrated the great contributions of Dr. Mundkur for the development of Plant Pathology in India. Also, I was taken to the place near Dharwad where Dr. Mundkur worked as Assistant mycologist in Cotton Research Station and his contributions were so impressive that I decided to opt for post graduate programme in Plant Pathology. I was very much impressed by his work pertaining to practical aspect and location specific problems of farmers. I salute Dr. Balachandra Bhavanishankar Mundkur whose work on plant pathology very much impressed and thus inspired me to take plant pathology as a career. Therefore, now I have choosen to talk on a topic which is location specific, problem of the farmers and economically significant. Also this approach of IDM for a soil borne polyphagous and pleurivorus pathogen would be an inspiration to the young scientists to develop similar IDM to solve the different problems. The topic is "Integrated Management of the Potato Sclerotium wilt caused by Sclerotium rolfsii " .